1989
DOI: 10.1111/j.1365-2273.1989.tb00414.x
|View full text |Cite
|
Sign up to set email alerts
|

A clinical and audiological investigation of osteogenesis imperfecta

Abstract: Fifty-six patients with osteogenesis imperfecta underwent clinical and audiological assessment. They completed questionnaires regarding their physical and otological disabilities, and attended various centres for audiological testing. It was found that 31 patients had a hearing loss. Hearing loss began in the second and third decades as a conductive loss, and progressed to a mixed loss. Eight patients, found in all age groups, had a pure sensorineural loss in one or both ears. Patients with osteogenesis imperf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
56
2

Year Published

1991
1991
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(62 citation statements)
references
References 15 publications
4
56
2
Order By: Relevance
“…On the other hand, this so-called characteristic high-frequency sensorineural loss was observed only sporadically in other OI populations 5,10,12 , as well as in ours, yielding a 1.4% prevalence of this isolated high-frequency pure sensorineural loss. More often, we observed a pure sensorineural loss involving the lower frequencies as well, affecting OI patients from all age categories, which is concordant with the findings of other large population studies [5][6][7]10 . Compared with the above-described conductive/mixed hearing loss, this pure sensorineural loss in OI seems to be characterized by a slower progression with less severely affected thresholds.…”
Section: Discussionsupporting
confidence: 80%
“…On the other hand, this so-called characteristic high-frequency sensorineural loss was observed only sporadically in other OI populations 5,10,12 , as well as in ours, yielding a 1.4% prevalence of this isolated high-frequency pure sensorineural loss. More often, we observed a pure sensorineural loss involving the lower frequencies as well, affecting OI patients from all age categories, which is concordant with the findings of other large population studies [5][6][7]10 . Compared with the above-described conductive/mixed hearing loss, this pure sensorineural loss in OI seems to be characterized by a slower progression with less severely affected thresholds.…”
Section: Discussionsupporting
confidence: 80%
“…Hearing loss in OI clinically resembles otosclerosis, but differs by earlier onset, more severe middle ear involvement, and a higher incidence of a sensorineural component [Shea et al, 1963;Shapiro et al, 1982;Stewart and O'Reilly, 1989;Garretsen et al, 1997;Kuurila et al, 2002]. Hearing loss in OI typically begins in early adulthood.…”
Section: Introductionmentioning
confidence: 95%
“…Population studies have revealed progressive hearing loss in up to 59% of adult OI patients [Seedorff, 1949;Smårs, 1961;Pedersen, 1984;Stewart and O'Reilly, 1989;Paterson et al, 2001;Kuurila et al, 2002]. Hearing loss in OI clinically resembles otosclerosis, but differs by earlier onset, more severe middle ear involvement, and a higher incidence of a sensorineural component [Shea et al, 1963;Shapiro et al, 1982;Stewart and O'Reilly, 1989;Garretsen et al, 1997;Kuurila et al, 2002].…”
Section: Introductionmentioning
confidence: 98%
“…Pure SNHL in OI is rare (10%) [Pedersen, 1985]. The hearing loss usually begins in the late teens, with the sensorineural component appearing in the third decade [Stewart and O'Reilly, 1989]. It gradually leads to profound deafness, tinnitus, and vertigo by the end of the forth to fifth decade [Pedersen, 1985].…”
Section: Introductionmentioning
confidence: 99%